把多项式(a+b-c)(a-b+c)-(b+c-a)(c-a-b)因式分解.求秒回!
2个回答
(a+b-c)(a-b+c)-(b+c-a)(c-a-b)
=(a+b-c)(a-b+c)+(b+c-a)(a+b-c)
=(a+b-c)(a-b+c+b+c-a)
=2c(a+b-c)
相关问题
求a(b+c-a)^2+b(c+a-b)^2+c(a+b-c)^2+(b+c-a)(c+a-b)(a+b-c)的因式分解
(c+a-b)(b+c-a)(a+b-c)+a(a-b+c)……因式分解
a²(b-c)+b²(c-5)+c²(a-b)因式分解
将下列多项式因式分解,并求值:a²-b²+c²+2ac,其中b=a+c
因式分解:(a-b-c)(a+b-c)+(b-c-a)(b+c-a)(注意是加号)
多项式a-b+c(a-b)因式分解的结果是
因式分解(a+b+c)³-a³-b³-c³
因式分解a3(b+c)+b3(a+c)+c3(a+b)+ab(a+b+c)
4a(b-c)²(b+c)+12a(c-b)³ 因式分解
已知A=a²+b²-3c²,B=-4a²+2b²+3c²,且A+B+C=0,求多项式C.